Double imprinted photoresponsive polymer for simultaneous detection of phthalate esters in plastics. (November 2018) - Gong, Cheng-bin; Wei, Yu-bo; Chen, Mei-jun; Liu, Lan-tao; Chow, Cheuk-fai; Tang, Qian
Graphical abstract: Highlights: Three ZnO@PSMIPs with different steric characteristics were synthesized for phthalate esters. Steric hindrance of azobenzene affects both photoresponsive and binding properties. Double-template imprinting is more effective for phthalate esters. ZnO@PSMIP1 was applied for simultaneous detection of phthalate esters in plastics. Abstract: A double-phthalate-ester imprinted photoresponsive polymer was fabricated for simultaneous detection of phthalate esters. Specifically, three azobenzene derivatives with different steric characteristics (0, 2, and 4 methyl substituents at the ortho position) were used as functional monomers, supported by ZnO nanoscale support rods. Dibutyl phthalate and dicyclohexyl phthalate esters were used as double templates. The three photoresponsive molecularly imprinted polymers were fabricated with a triethanolamine trimethacrylate ester cross-linker, and were characterized by ultraviolet–visible absorption, Fourier-transform infrared spectroscopy, scanning and transmission electron microscopy, and N2 adsorption–desorption analysis. Steric hindrance affected both photoresponsive properties and binding properties. As the steric hindrance increased, the trans → cis rate constant and the binding capacities decreased. Hence, the polymer with the least steric hindrance was used for the simultaneous detection of phthalate esters in plastic cups and toys. The doubly imprinted polymer was more effective for detection or extraction of the phthalate esters than was a single-phthalate-ester imprinted polymer.